NETIZENS’ STRATEGIES IN LEARNING VOCABULARIES FROM THE CONTEXT OF PREFERRED SOCIAL MEDIA POSTS: NA - Butac, Susan; JAWILI-DECENA, ANNALYN (International Journal of Arts, Sciences and Education, 2022)
People of different ages may acquire new words from various online sources each day in this digital age. Since Facebook seems to be the most widely-used social media platform, the researchers investigated netizens’ preferred social media posts and their strategies in learning new vocabulary. This Quantitative Descriptive Survey research was participated in by two hundred thirty (230) netizens composed of one-hundred twenty-eight (128) students, sixty-tw0 (62) public school teachers, nine (9) government employees (outside teaching), nine (9) private school teachers, nine (9) unemployed individuals, five (5) employed in a private sector, five (5) self-employed, two (2) housewives(homemakers), and one (1) OFW. The study used a closed-ended researcher-made survey questionnaire that contained questions about their most preferred social media posts and their strategies to learn new words. It used frequency and percentage in dealing with numeric data; this study found that netizens prefer to read posts of professionals, like teachers and celebrities. They prefer to read status/posts in English and learn new English words. The strategies they apply involve copying (writing) the status on their notes, emphasizing the new word/s learned. The respondents also memorize the new words learned (Bottom-Up), share status using the new vocabulary in their context/s (Top-Down), join in the conversation on Facebook or face-to-face with friends and colleagues using the new words learned (Interactive). The study concluded that even professionals and adults are interested in learning new words each day. The researchers encourage teachers to use online platforms like Facebook to introduce new vocabulary/words. Posting educational messages would help promote new vocabulary learning. As much as possible, their status should be in the target language. Keywords: social media platform, top-down, bottom-up, interactive, vocabulary learning